An investigation into the diet of elephant fish ( Callorhinchus milii ) in the waters of Aotearoa/New Zealand - Kat U. C. Cooper; Ashley A. Rowden; Darren Stevens; Brittany Finucci (Journal of Fish Biology, 2026)
Chondrichthyans (sharks, rays and chimaeras) are increasingly understood to be an important part of ocean ecosystems, but their ecological role is unclear. Callorhinchus milii (elephant fish) is a chimaera species endemic to Aotearoa/New Zealand and southern Australian waters. Its trophic ecology is poorly defined, despite its commercial and recreational importance across much of its range. This study used stomach content analysis to generate a more comprehensive understanding of the diet of C. milii , and to identify biological and/or environmental predictors that may explain any variation in diet. Crustaceans, in particular pagurids and brachyurans, such as Lophopagurus spp. and leucosiid crabs, were the most important prey type (56% index of relative importance, IRI), followed by molluscs (30% IRI). The single most important prey type was leucosiid crabs, which occurred in nearly half of all digestive tracts and had a %IRI of 26%. Depth was found to be the greatest predictor of variation in C. milii diet, with samples taken from greater depths containing more bivalve molluscs and polychaetes, and those from shallower depths containing more gastropod molluscs and brachyuran crabs. These findings were consistent with studies of other shallow water callorhinchids and deep‐water chimaeras around the world. While C. milii have been identified as at risk from climate change, the findings of this study suggest a flexible, generalist diet that may provide some resilience to environmental change caused by anthropogenic impacts.